Liver Transcriptome and Gut Microbiome Analysis Reveals the Effects of High Fructose Corn Syrup in Mice - Shen, Yu; Sun, Yangying; Wang, Xiaoli; Xiao, Yingping; Ma, Lingyan; Lyu, Wentao; Zheng, Zibin; Wang, Wen; Li, Jinjun (Frontiers in Nutrition, 2022)
High fructose corn syrup (HFCS) is a viscous mixture of glucose and fructose that is used primarily as a food additive. This article explored the effect of HFCS on lipid metabolism-expressed genes and the mouse gut microbiome. In total, ten 3-week-old male C57BL/6J mice were randomly divided into two groups, including the control group, given purified water (Group C) and 30% HFCS in water (Group H) for 16 weeks. Liver and colonic content were collected for transcriptome sequencing and 16S rRNA gene sequencing, respectively. HFCS significantly increased body weight, epididymal, perirenal fat weight in mice (p < 0.05), and the proportion of lipid droplets in liver tissue. The expression of the ELOVL fatty acid elongase 3 (Elovl3) gene was reduced, while Stearoyl-Coenzyme A desaturase 1 (Scd1), peroxisome proliferator activated receptor gamma (Pparg), fatty acid desaturase 2 (Fads2), acyl-CoA thioesterase 2 (Acot2), acyl-CoA thioesterase 2 (Acot3), acyl-CoA thioesterase 4 (Acot4), and fatty acid binding protein 2 (Fabp2) was increased in Group H. Compared with Group C, the abundance of Firmicutes was decreased in Group H, while the abundance of Bacteroidetes was increased, and the ratio of Firmicutes/Bacteroidetes was obviously decreased. At the genus level, the relative abundance of Bifidobacterium, Lactobacillus, Faecalibaculum, Erysipelatoclostridium, and Parasutterella was increased in Group H, whereas that of Staphylococcus, Peptococcus, Parabacteroides, Donghicola, and Turicibacter was reduced in Group H. Pparg, Acot2, Acot3, and Scd1 were positively correlated with Erysipelatoclostridium and negatively correlated with Parabacteroides, Staphylococcus, and Turicibacter. Bifidobacterium was negatively correlated with Elovl3. Overall, HFCS affects body lipid metabolism by affecting the expression of lipid metabolism genes in the liver through the gut microbiome.